Xylan-regulated delivery of human keratinocyte growth factor-2 to the inflamed colon by the human anaerobic commensal bacterium Bacteroides ovatus. Issue 4 (7th September 2009) - Hamady, Zaed Z R; Scott, Nigel; Farrar, Mark D; Lodge, J Peter A; Holland, Keith T; Whitehead, Terence; Carding, Simon R
Abstract : Background: Human growth factors are potential therapeutic agents for various inflammatory disorders affecting the gastrointestinal tract. However, they are unstable when administered orally and systemic administration requires high doses increasing the risk of unwanted side effects. Live microorganism-based delivery systems can overcome these problems although they suffer from the inability to control heterologous protein production and there are concerns regarding biosafety and environmental contamination. Methods: To overcome these limitations we have developed a new live bacteria drug-delivery system using the human commensal gut bacterium Bacteroides ovatus engineered to secrete human growth factors in response to dietary xylan. The anaerobic nature of B ovatus provides an inherent biosafety feature. B ovatus strains expressing human keratinocyte growth factor-2, which plays a central role in intestinal epithelial homeostasis and repair (BO-KGF), were generated by homologous recombination and evaluated using the dextran sodium sulfate (DSS)-induced model of intestinal epithelial injury and colitis. Results: In response to xylan BO-KGF produced biologically active KGF both in vitro and in vivo. In DSS treated mice administration of xylan and BO-KGF had a significant therapeutic effect in reducing weight loss, improving stool consistency, reducing rectal bleeding, accelerating healing of damaged epithelium, reducing inflammation and neutrophil infiltration, reducing expression of pro-inflammatory cytokines, and accelerating production of goblet cells. BO-KGF and xylan treatment also had a marked prophylactic effect limiting the development of inflammation and disruption of the epithelial barrier. Conclusion: This novel, diet-regulated, live bacterial drug delivery system may be applicable to treating various bowel disorders.